The forgotten APOE allele: a review of the evidence and suggested mechanisms for the protective effect of APOE ɛ2. - Suri, S; Heise, V; Trachtenberg, A; Mackay, C (2013)
Ongoing efforts to improve survival, and enhance quality of life have led biomedical research to focus on disease and the mechanisms that increase risk for disease. The other side of that coin may be as important, i.e. examining the protective factors that allow some individuals to enjoy long, healthy lives. One of the best examples of a gene that positively influences cognitive health is the apolipoprotein (APOE) ɛ2 allele. The APOE ɛ4 allele is a well-established risk factor for Alzheimer's disease (AD) and has thus dominated the APOE literature, with the putative protective role of ɛ2 receiving little attention. This review describes the effects of APOE ɛ2 on the structure and function of the brain. With a focus on neurodegeneration, we discuss evidence for APOE ɛ2's protective effects, explore some key mechanisms through which this protection may be conferred, and address a few inconsistencies in the literature. Understanding the mechanisms that underlie the association between APOE ɛ2, cognition and longevity may provide new targets for research on promoting life-long health.